Job satisfaction of the nephrology department staff of the Hospital Guillermo Kaelin de la Fuente, Villa María, 2019 - Holguin Morales, Yojani (2020)
Objective: To identify the level of job satisfaction of the nephrology department staff of the Hospital Guillermo Kaelin de la Fuente, Villa María, in 2019. Materials and methods: An analytical study was conducted. The nephrology department consists of 76 staff members, out of which 40 (52.64 %) took part in the study (physicians, registered nurses, nurse technicians, administrative staff, etc.). The extrinsic and intrinsic dimensions of job satisfaction were evaluated. The data was processed using SPSS Statistics statistical software, version 24.00. Results: The staff members were relatively young (mean age: 38.8 years; SD: ± 6.8) and females slightly prevailed (67.50 %). Twenty-eight percent (28 %) of the staff members had high levels of satisfaction. The study participants who started working in the hospital from its creation (job tenure ≤ 3 years) showed higher levels of job satisfaction than those with a job tenure between 4 and 6 years. Eighty-six point seven percent (86.7 %) of staff members who worked less than 3 years showed higher levels of medium-high satisfaction than those who worked between 4 and 6 years (68 %). Conclusions: Twenty-eight percent (28 %) of the staff members had a high level of job satisfaction, out of whom physicians showed the highest level of satisfaction (83.3 %). Forty-eight percent (48 %) had a medium level of job satisfaction and one out of four staff members showed a low level of satisfaction. Staff members with a job tenure ≤ 3 years had the highest level of job satisfaction: the shorter the job tenure, the greater the job satisfaction. Apparently, job satisfaction “fades away” as years pass.